The Six W-Questions at the Heart of Strategic Planning for the Development of School Organizations - Rumyana Gyoreva (Педагогически форум)
Strategic planning is a key management activity of school organizations. It enables management to find adequate answers to the problems caused by changes in the external environment that require long-term solutions. The article analyzes the main aspects of the nature and implementation of strategic planning in schools. The emphasis is on developing the strategy of the school using the approach of questions. The analysis shows how the method of W-questions can facilitate a strategy for the development of school institutions as an action plan, the roadmap, which sets priorities in response to the expectations of students, parents and society.